"Evidence"‐based medicine in eating disorders research: The problem of "confetti p values". Issue 3 (23rd February 2017) - Chmura Kraemer, Helena
Abstract: Eating disorders hold a unique place among mental health disorders, in that salient symptoms can be objectively observed and measured rather than determined only from patient interviews or subjective evaluations. Because of this measurement advantage alone, evidence‐based medicine would be expected there to make the most rapid strides. However, conclusions in Eating Disorders research, as in all medical research literature, often continue to be misleading or ambiguous. One major and long‐known source of such problems is the misuse and misinterpretation of "statistical significance", with " p values" strewn throughout research papers like so much confetti, a problem that has become systemic, that is, enforced, rather than corrected, by the peer‐review system. This discussion attempts to clarify the issues, and to suggest how readers might deal with this issue in processing the research literature.